Association of living alone with the presence of undiagnosed diabetes in Japanese men: the role of modifiable risk factors for diabetes: Toranomon Hospital Health Management Center Study 13 (TOPICS 13). Issue 11 (9th July 2013) - Heianza, Y.; Arase, Y.; Kodama, S.; Hsieh, S. D.; Tsuji, H.; Saito, K.; Shimano, H.; Hara, S.; Sone, H.
Abstract Aims To investigate whether living alone was associated with the presence of undiagnosed diabetes and whether this association could be attenuated by modifiable lifestyle habits. Methods This cross‐sectional study included 6400 Japanese men without a history of diagnosed diabetes. Individuals with currently undiagnosed diabetes were identified through fasting glucose concentration ≥7.0 mmol/l or HbA1c concentration ≥ 48 mmol⁄mol (≥ 6.5%). Effect modification was examined using body mass index, hypertension, history of dyslipidaemia, drinking habits, smoking habits, physical activity, vegetable intake, emotional stress and depressed mood. Results Men who lived alone (n = 1098) had a significantly elevated odds ratio for having undiagnosed diabetes in an age‐adjusted model (odds ratio 1.45, 95% CI 1.07, 1.96; P = 0.018). After adjustment for lifestyle factors, the association was slightly attenuated (odds ratio 1.40, 95% CI 1.02, 1.91; P = 0.036). After further adjustment for all factors mentioned above, living alone was still marginally significantly associated with the presence of undiagnosed diabetes (odds ratio 1.38, 95% CI 1.003, 1.90; P = 0.048). A significant association of living alone with the presence of undetected diabetes was particularly observed among men who were overweight, currently smoked and were physically inactive, or had any one of those three factors. Conclusions The association between undiagnosed diabetes and living alone can be partially influenced by modifiable lifestyle factors. Men who lived alone, especially those who did not engage in favourable lifestyle habits, were more likely to have undiagnosed diabetes. Such individuals have a higher probability of having undetected diabetic hyperglycaemia and would need to undergo glucose tests to identify the disease.